Subclinical Hypothyroidism and the Alterations of Lipid Profile as a Cardiovascular Risk Factor - Maleki, Narges; Kazerouni, Faranak; Hedayati, Mehdi; Rahimipour, Ali; Parham, Mahmoud (Archives of Advances in Biosciences, 2015)
The association between overt hypothyroidism and altered lipid profile is well known, whereas the significance of dyslipidemia in subclinical hypothyroidism (SCH) is still a matter of debate. The aim of the present study was to evaluate the lipid profile in patients with SCH in comparison to controls. Serum lipid parameters of 34 patients with SCH and 34 age- and sex-matched healthy controls were evaluated in our study. TC (198.88 ± 42.90 vs 171.40 ± 26.24 mg/dl, P < 0.01) and LDL-C concentrations (129.04 ± 35.44 vs 106.71 ± 26.21 mg/dl, P < 0.01) as well as ratio of LDL-C/HDL-C (3.51 ± 1.46 vs 2.81 ± 0.80, P < 0.05) were significantly higher in the patients in comparison to the controls, whereas HDL-C and TC/HDL-C ratio remained unaltered. TG concentrations were higher in the patients but this difference did not reach statistical significance (0.063). Correlation analyses revealed a significant correlation of TSH with TC, LDL-C and LDL-C/HDL-C ratio (r=0.351, r=0.345, r=0.340, respectively, P < 0.01) and a borderline correlation with TG (p=0.051). Our findings showed that SCH is associated with some lipid abnormalities suggesting higher risk of cardiovascular disease in these patients which seems to weigh in favor of treatment of patients with SCH.